MODEL ADSORPSI LANGMUIR GAS DINITROGEN MONOKSIDA DALAM SISTEM BIOFILTER DENGAN MEDIUM PUPUK KOMPOS - Tania Surya Utami; Josia Simanjuntak; Heri Hermansyah; Mohamad Nasikin (Dept. of Chemical Engineering, Diponegoro University, 2011)
LANGMUIR ADSORPTION MODEL FOR DINITROGEN MONOXIDE IN BIOFILTER SYSTEM USING COMPOST FERTILIZER MEDIUM. Nitrous oxide (N2O) is mostly emitted from various industrial processes and agricultural activities. This gas causes serious environmental problems and is considered as a dangerous pollutant. In the past, traditional control technologies, such as Selective Catalytic Reduction (SCR) and Selective Non-Catalytic Reduction (SNCR), were applied to control N2O emissions in some industries. However, these two processes required high temperatures and the use of catalysts. Economic and technical constraints in SCR and SNCR methods motivated researchers to develop new, cost-effective processes to remove N2O. Biofiltration is an emerging technology that offers a number of advantages over traditional methods of air pollution control. The purpose of this research is to modelise the biofiltration experimental results into the Langmuir adsorption model. This research is conducted in laboratory scale biofilter column, with parameters studied are effect of biofilter length and N2O gas flowrate. The result of the model is simulated into sensitivity analysis. The average Langmuir constant obtained in the model of the research is 16.006 liter/mol. Dinitrogen Monoksida (N2O) merupakan emisi dari proses industri dan kegiatan pertanian. Gas tersebut merupakan gas polutan berbahaya dan menyebabkan masalah lingkungan yang serius. Sebelumnya, teknologi kontrol tradisional seperti Selective Catalytic Reduction (SCR) dan Selective Non-Catalytic Reduction (SNCR) digunakan untuk mengontrol emisi N2O pada kegiatan-kegiatan industri. Akan tetapi, kedua proses ini membutuhkan suhu yang tinggi dan penggunaan katalis. Adanya masalah dari segi ekonomi dan teknis memotivasi peneliti untuk mengembangkan teknologi baru yang lebih murah dan efisien untuk menghilangkan N2O dari gas buangan. Pengolahan N2O secara biologis dalam proses biofiltrasi adalah salah satu alternatif ramah lingkungan yang dapat digunakan dalam pengelolaan emisi industri. Penelitian ini bertujuan untuk menggambarkan hasil biofiltrasi gas N2O dengan medium pupuk kompos dalam bentuk model adsorpsi Langmuir. Penelitian dilakukan dalam kolom biofilter skala laboratorium, dan parameter-parameter yang diteliti adalah pengaruh dari ketinggian biofilter dan laju alir gas N2O. Hasil dari pemodelan kemudian disimulasikan dalam analisis sensitivitas. Nilai konstanta Langmuir rata-rata yang didapatkan dari pemodelan penelitian ini adalah 16,006 liter/mol.